Influence of Fiscal and Monetary Policy of Kazakhstan on Modernization and Economic Growth in the Conditions of Globalization - KUCHUKOVA, Nurilya; TURARBEKOV, Mereke; AGUMBAYEVA, Assiya (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article considers the issues of influence of fiscal and monetary policy of Kazakhstan on modernization, diversification and innovation through taxes, public expenditures and budget deficit regulation and other regulation tools in the conditions of negative influence of external factors caused by globalization processes. The research object is an influence of the fiscal and monetary policy measures on the economic growth of Kazakhstan. The authors are successful in analyzing the most important trends in the global economic, revealing their influence on the national economy and making recommendations for improving of fiscal and monetary policy in Kazakhstan. The article distinguishes the influence of the state budget income and expenditure policy on modernization, industrialization, innovation and economic growth stimulation of Kazakhstan. The research is based on system analysis assuming the structural and functional approach consisting in segregation of structural elements in system objects and identification of their role (functions) in the system.
Keywords: modernization, competitive ability, integration, globalization, strategy, policy